Dante Gabriel Rossetti - Johnston, Robert DeSales (Twayne Publishers, 1969)
Provides in-depth analysis of the life, works, career, and critical importance of Dante Gabriel Rossetti
Includes bibliographical references and index
Keywords: Rossetti; Dante Gabriel; English literature; Authors; English